2005
DOI: 10.2223/jped.1288
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmomyiasis as a cause of canalicular lesion

Abstract: Objetivo: Miíase é a invasão de tecido humano pela larva de uma mosca da ordem Díptera. O envolvimento ocular não é comum. Lesões do aparelho lacrimal geralmente estão associadas a traumas e raramente são devidas a infestações parasitárias. O objetivo deste trabalho é relatar um caso de laceração canalicular causado por larva de Dermatobia hominis.Descrição: Criança do sexo feminino, 8 anos de idade, apresentou-se com celulite pré-septal não responsiva a antibioticoterapia. Foi observada uma larva de D. homini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The one retrospective review found 6.15% of external ophthalmomyiasis cases occurred in individuals younger than 5 years. 37 The clinical manifestations of external ophthalmomyiasis fell into 3 groups: lid myiasis (48.6%), 24,27,39,46,62,79,101,114,116,120,122,129,139,158 ocular surface myiasis (45.9%), 5,15,22,39,44,65,66,84,104,115,130,138,145,150,166 and orbital infestation (25.4%). 41,129 The mean age for the overall cohort was 9.1 years (range, 12 days to 17 years).…”
Section: Beesmentioning
confidence: 99%
See 1 more Smart Citation
“…The one retrospective review found 6.15% of external ophthalmomyiasis cases occurred in individuals younger than 5 years. 37 The clinical manifestations of external ophthalmomyiasis fell into 3 groups: lid myiasis (48.6%), 24,27,39,46,62,79,101,114,116,120,122,129,139,158 ocular surface myiasis (45.9%), 5,15,22,39,44,65,66,84,104,115,130,138,145,150,166 and orbital infestation (25.4%). 41,129 The mean age for the overall cohort was 9.1 years (range, 12 days to 17 years).…”
Section: Beesmentioning
confidence: 99%
“…41 The culprit larva was identified in 83.3%% of lid myiasis cases, 67.4% of ocular surface cases, and in 1 of the 2 orbital cases. Dermatobia hominis was the most common larva to cause lid myiasis (8 of 14 cases) 46,114,120,122,158 followed by Cuterebra larva (3 of 14 cases). 62,79,116 There were single lid myiasis cases of Chrysomya bezziana, 24 Lucilia, 27 reindeer Warble fly, 139 and Wohlfahrtia magnifica.…”
Section: Beesmentioning
confidence: 99%
“…It is more likely to occur in the subsection of the population who face social isolation and especially in those consuming alcohol regularly. [7][8][9] Ophthalmomyiasis is termed as external, when the involvement is limited to the superficial periocular tissues including the palpebral and conjunctival myiasis without sclera or conjunctival penetration. Once it penetrates the conjunctiva or sclera and migrates to the subretinal space, it is termed as internal ophthalmomyiasis.…”
Section: Discussionmentioning
confidence: 99%
“…11). The life cycle is very complex and requires a flying arthropod to transport its eggs to a mammalian vertebrate, which include cattle, dogs, cats, pigs and man (Sancho 1988;Pereira Da Silva et al 1998;Brizuela et al, 2003;Maier and Honigsmann 2004;Saraiva et al 2005). The adult fly is bottle blue in colour.…”
Section: Dermatobia Hominismentioning
confidence: 99%